Replacement Of The Interocclusal Space Lost After Preparatıon Wıth An Orthodontıc Applıcatıon - Hakan N. İşcan; Nezihi Bayık; Tunç Akman (Galenos Yayinevi, 1988)
Interocclusal space achieved by the preparation of the teeth for the fixed prosthetic restorations could be lost with the extrusion of those teeth when a considerable elapse of time happened to be between the preparation of the teeth and the cementation of the restoration according to the negligence of either the clinician or the patient In this case report, the application in two cases with the treatment results of an orthodontic appliance designed to use in the replacement of the interocclusal space without necessitating a secondary preparation however by the intrusion of the extruded teeth were presented. By means of this removable upper jaw orthodontic appliance; upper right first premolar and third molar in a fifty-two years old male patient and lower left and right second premolars and molars in a twenth-two years old female patient were intruded within approximately three months and thus the interocclusal space were regained. The cephalometric evaluation of the tooth movements were determined on the lateral and postero-anterior cephalometric films.